Polycyclic aromatic hydrocarbon growth in a benzene discharge explored by IR-UV action spectroscopy. Issue 24 (13th June 2022) - Lemmens, Alexander K.; Rap, Daniël B.; Brünken, Sandra; Buma, Wybren Jan; Rijs, Anouk M.
Abstract : IR-UV spectroscopy of a benzene discharge reveals larger PAHs and intermediates showing that different gas-phase PAH growth mechanisms can occur under the same conditions. The identifications are promising candidates for radio astronomy searches. Abstract : Infrared signatures of polycyclic aromatic hydrocarbons (PAHs) are detected towards many phases of stellar evolution. PAHs are major players in the carbon chemistry of the interstellar medium, forming the connection between small hydrocarbons and large fullerenes. However, as details on the formation of PAHs in these environments are still unclear, modeling their abundance and chemistry has remained far from trivial. By combining molecular beam mass-selective IR spectroscopy and calculated IR spectra, we analyze the discharge of benzene and identify resulting products including larger PAHs, radicals and intermediates that serve as promising candidates for radio astronomical searches. The identification of various reaction products indicates that different gas-phase reaction mechanisms leading to PAH growth must occur under the same conditions to account for all observed PAH-related species, thereby revealing the complex and interconnected network of PAH formation pathways. The results of this study highlight key (exothermic) reactions that need to be included in astrochemical models describing the carbon chemistry in our universe.